Management of COVID-19 through Ayurveda Perspective – A Case Report - Sahu, Tripura (International Research Journal of Ayurveda & Yoga, 2025)
COVID-19 has become a global Pandemic since 2020 and multiple treatments such as antivirals, steroids, immunomodulators, with vaccines have been developed and marketed, but the treatment modality has not been fully confirmatory toward all the systemic and symptomatic relief in patients. Furthermore, there are limitations for all the designed and developed treatment protocols and post-treatment complications as respiratory distress, low immunity, allergic reactions, cardiac arrest, etc. To avoid such complications and improve the quality of life in COVID-19 patients Ayurvedic treatment principles can be taken into consideration. This is an effort to share experience in a case of COVID-19 management through Ayurveda. A pre-diagnosed COVID-19 case with complaints of chronic dry cough, anorexia, and anosmia who has undergone steroidal and antiviral treatment, but there is no improvement, so the patient approached Ayurveda. In Ayurveda, COVID-19 can be correlated with Pranavaha Srotas Vikara as it mainly affects the respiratory system. On the basis of history and examination, the samprapti of the disease was found to be caused by Garavisha (agantuka nidan), leading to Ama, srotorodha(pranavaha and rasavaha), in turn resulting in vata-kapha vriddhi, so treatment was planned accordingly. Case was managed with oral medicines such as Indukanta Kasaya, Shwasa-Kasa chintamanirasa, Shwasamrita syrup, Abhrakabhasma + Shitopaladichoorna + Yastimadhuchurna with Madhu, Agastya rasayanam for Muhurmuhu. After 5 days dry cough reduced, appetite improved and subjective recovery was observed. Same continued for 15 days and all the symptoms were completely reduced, smell and taste recovered after 1 month.